MORPHOLOGY OF HUMAN GENITAL “T-STRAIN” PLEUROPNEUMONIA-LIKE ORGANISMS - Ford, Denys K. (1963)
Ford, Denys K. (University of British Columbia, Vancouver, Canada), and Joyce Macdonald. Morphology of human genital “T-strain” pleuropneumonia-like organisms. J. Bacteriol. 85:649–653. 1963.—The morphology of Shepard's “T-strain” organisms from the human genital tract was investigated. The incubation of “T-strains” in 20% CO(2) with 80% nitrogen for 4 to 5 days caused surface outgrowth from the central core of the colonies embedded in the agar. Filtration through HA, PH, and VC Millipore filters showed that the elementary particles of “T-strains” were between 0.3 and 0.1 μ in diameter. “T-strain” pleuropneumonia-like organisms (PPLO) from broth cultures, stained by Giemsa's method, were seen to be minute, spherical particles, similar in size to the particles of the large-colony strains. Colonies of “T-strains,” when prepared by the microculture, fixed-agar-block, and Formvar methods, resembled those of large-colony PPLO. It was concluded that “T-strain” organisms were true PPLO.